لغة اهل القانون التحريرية والشفوية: اهم القواعد النحوية والصرفية والاملائية والاسلوبية والخطابية لدى القانوني - د. معن عبد القادر بشير (PROSPECTIVE RESEARCHES, 2023)
Any law specialist, whether a lawyer, a judge or a legislator, needs to possess a special linguistic talent in order to be able to perform correctly during a tried or when legislating a new law. In this research, we have dealt with selections from grammar and morphology, which are essential for any lawyer. We also talked about spelling, composition and style, in addition to speech making, shedding light on the effect of these issues on legal dialogues.